Metaplasmos: a evolução fonética da Língua portuguesa - SANTOS, Gleice Simone Nunes dos (2023)
The main goal of this work is to analise the phonetical variations through the metaplasms in the magazine turma do Chico bento. The object of this article is the phonetical variation presents in the speech of the characters that represents the dialectof a rural society. It will be make an approachof the Portuguese history to be explained in a coherent way the origens, evolution abd transformation of our language. The methodological procedures conducted to this research were: pick the magazine, after that, it weas chosen 52 words from the magazine, andthen the words were analyzeddetailed, noticing the phonetical variation and classified in the metaplasms groups.